2014
DOI: 10.1097/prs.0000000000000564
|View full text |Cite
|
Sign up to set email alerts
|

The Fusion of Craniofacial Reconstruction and Microsurgery

Abstract: Craniofacial surgery, like plastic surgery, has made tremendous advancements in the past 40 years. With innovations in technology, flap design, and training, microsurgery has become safer, faster, and more commonplace than at any time in history. Reconstructive microsurgery allows the surgeon to be creative in this approach, and free tissue transfer has become a mainstay of modern craniofacial reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 83 publications
0
18
0
1
Order By: Relevance
“…Defects in the craniofacial region in particular are difficult to treat because of the emphasis on positive aesthetic outcomes and the number of tissue types (bone, cartilage, muscle, and skin) and structures (auricle, orbit, nose, oral cavity) in close proximity. The current options for reconstructive surgery to treat these defects include grafts, local tissue rearrangement which fills defects with adjacent healthy tissue, microsurgical tissue transfer whereby one area of the body is transferred with its blood supply to another area 10,22 , and vascularized composite allotransplantation whereby a portion of the body containing skin, muscle and/or bone is transplanted from one patient to another 16 . However, the major challenges with using traditional reconstructive surgery to treat large craniofacial defects are donor-site morbidity and procuring sufficient donor tissue with the same properties, including skin color, quantity and contour of bone, and quantity and quality of subcutaneous tissues, as the surrounding recipient tissue to restore normal anatomic structure and primary organ functions.…”
Section: Introductionmentioning
confidence: 99%
“…Defects in the craniofacial region in particular are difficult to treat because of the emphasis on positive aesthetic outcomes and the number of tissue types (bone, cartilage, muscle, and skin) and structures (auricle, orbit, nose, oral cavity) in close proximity. The current options for reconstructive surgery to treat these defects include grafts, local tissue rearrangement which fills defects with adjacent healthy tissue, microsurgical tissue transfer whereby one area of the body is transferred with its blood supply to another area 10,22 , and vascularized composite allotransplantation whereby a portion of the body containing skin, muscle and/or bone is transplanted from one patient to another 16 . However, the major challenges with using traditional reconstructive surgery to treat large craniofacial defects are donor-site morbidity and procuring sufficient donor tissue with the same properties, including skin color, quantity and contour of bone, and quantity and quality of subcutaneous tissues, as the surrounding recipient tissue to restore normal anatomic structure and primary organ functions.…”
Section: Introductionmentioning
confidence: 99%
“…Broyles et al . . reported that there were no statistically significant differences of two‐point discrimination sensitivity and cold/hot discrimination between innervated RFFFs and the contralateral side of the flaps indicating a complete sensory recovery for these sensory modalities in the reinnervated RFFF.…”
Section: Discussionmentioning
confidence: 98%
“…1 However, the importance of aesthetic results must not be overlooked. Intraoral anastomosis not only precludes the need for a skin incision, but also identifies the facial nerve branches and avoids web 4C=FPO 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 284 285 286 287 288 289 290 291 292 293 294 295 296 297 298 299 300 301 302 303 304 305 306 307 308 309 310 311 312 313 314 315 316 317 318 319 320 321 322 323 324 325 326 327 328 329 330 331 332 333 334 335 336 inadvertent injury.…”
Section: Discussionmentioning
confidence: 99%
“…Vascularized composite free tissue transfers offer unique reconstructive solutions for complex anatomic deformities. 1 Midface deformities are particularly challenging owing to the loss of composite tissue, including bone, soft tissue, and the mucosal lining, effectively impairing function and aesthetics. Commonly, the need for reconstruction follows oncologic resection or facial trauma, allowing for extraoral microvascular anastomoses to be completed using a facial skin incision already created during tumor resection or during the traumatic event.…”
mentioning
confidence: 99%